1987
DOI: 10.1111/j.1460-2466.1987.tb00996.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Analysis and the Construction of News

Abstract: Just as Chicken Little did in warning that "he sky is falling '' the news media cornrnitfindamentd errors of ath-ibution in their coverage of risk situations, by treating them as rwvelties, failing to analyze the entire system, and using im@ciently analytical language.The sky has n e z w fallen and nezw tctll. Thozigh the sky has nezw fallen, it zcdl inezttably full. The likelihood of the skjj jalling increases etlery day. Our sky is beginning to shou~ eziidence of fulling. Someone sau' apiece oj-the sky full … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
3

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(47 citation statements)
references
References 11 publications
1
41
0
3
Order By: Relevance
“…In this study, newspapers reported the dangers that could occur to infants if they were not weaned at a certain time but the reporting of weaning displayed many of the flaws of previous risk reporting, including not placing the risk in its proper context and not using the correct linguistic tools, such as risk comparisons to describe the level of risk to infants (Wilkins and Patterson, 1987;Rowe et al, 2000). Indeed, in the comparison between the newspaper articles and the Internet forum, no newspaper article discusses risk adequately, in comparison to over a third of the forum discussions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, newspapers reported the dangers that could occur to infants if they were not weaned at a certain time but the reporting of weaning displayed many of the flaws of previous risk reporting, including not placing the risk in its proper context and not using the correct linguistic tools, such as risk comparisons to describe the level of risk to infants (Wilkins and Patterson, 1987;Rowe et al, 2000). Indeed, in the comparison between the newspaper articles and the Internet forum, no newspaper article discusses risk adequately, in comparison to over a third of the forum discussions.…”
Section: Discussionmentioning
confidence: 99%
“…News has been variously characterized by consequence, immediacy, prominence, oddity, and proximity (Gibson, 1984) as well as by conflict, change, action, concreteness, and personality (Metzler in Wilkins & Patterson, 1987). Organizational crisis will often embody many, if not all of these elements.…”
Section: Sensemaking As Ongoingmentioning
confidence: 99%
“…In McMullan's claim that news narratives are "highly selective, interpretive and profoundly invented" (2001, p. 132), he notes the reliance on experts, professionals, and their agents. In their analysis linking risk and news construction, Wilkins & Patterson (1987) refer to the tendency to "line up the usual suspects . .…”
Section: Sensemaking and Identity Constructionmentioning
confidence: 99%
“…Much environmental news coverage is event-centered (Anderson, 1997:121). Several researchers found that the news media are preoccupied with dramatic events such as oil spills and to a lesser extent, pseudo events such as publicity stunts (Anderson, 1991, Wilkins andPatterson, 1987;Sachsmon, 1976;Molotech andLaster 1974, Rubin andSachs 1973).…”
Section: Review Of Literaturementioning
confidence: 99%